Rostral Anterior Cingulate Cortex–Ventrolateral Periaqueductal Gray Circuit Underlies Electroacupuncture to Alleviate Hyperalgesia but Not Anxiety-Like Behaviors in Mice With Spared Nerve Injury - Zhu, Xixiao; Xu, Yingling; Shen, Zui; Zhang, Haiyan; Xiao, Siqi; Zhu, Yichen; Wu, Mengwei; Chen, Yeqing; Wu, Zemin; Xu, Yunyun; He, Xiaofen; Liu, Boyu; et al. (Frontiers in Neuroscience, 2022)
Neuropathic pain is a common cause of chronic pain and is often accompanied by negative emotions, making it complex and difficult to treat. However, the neural circuit mechanisms underlying these symptoms remain unclear. Herein, we present a novel pathway associated with comorbid chronic pain and anxiety. Using chemogenetic methods, we found that activation of glutamatergic projections from the rostral anterior cingulate cortex (rACCGlu) to the ventrolateral periaqueductal gray (vlPAG) induced both hyperalgesia and anxiety-like behaviors in sham mice. Inhibition of the rACCGlu-vlPAG pathway reduced anxiety-like behaviors and hyperalgesia in the spared nerve injury (SNI) mice model; moreover, electroacupuncture (EA) effectively alleviated these symptoms. Investigation of the related mechanisms revealed that the chemogenetic activation of the rACCGlu-vlPAG circuit effectively blocked the analgesic effect of EA in the SNI mice model but did not affect the chronic pain-induced negative emotions. This study revealed a novel pathway, the rACCGlu-vlPAG pathway, that mediates neuropathic pain and pain-induced anxiety.